Statutory adjudication under CIPAA 2012 - Ali Mohamed, Ashgar Ali; Kasi, Arun (The Malaysian Current Law Journal Sdn Bhd, 2020)
Payment disputes in the construction industry has been something peculiar compared to many other industries. In the construction industry, it is common that payment is made progressively upon progress payment certificates. However, when an employer refuses to pay for whatsoever reason, this puts the contractor in a dilemma. This is because if the contractor stops or slows down work, the contractor may be found to be in breach if ultimately, it turns out that the employer has rightfully disputed the payment. At the same time, to go on with the work without payment pending time-consuming resolution of the dispute through courts with multiple layers of appeal or arbitration, could put the contractor in great financial distress. Not only that, the contractor may face the risk of continued default by the employer if he goes on to carry out the work